Minutes of the Second Regular Meeting of the Rocky Mountain Coal-Mining Institute. HELD AT Salt Lake City, .Utah June 11, 12 and 13, 1913 (Rocky Mountain Coal Mining Institute, 1913)
JUNE 11-MORNING SESSION The meeting was called to order Wednesday morning, June 11, 1913,,at 10 o'clock, by the President, E. H. Weitzel. Addresses of welcome were given to the convention by Governor Spry, Mayor Park, and Rev. P. A: Simpkins; 'the several addresses being interspersed by music. The session adjourned at 11 :50 a. m., in order to attend the organ recital at the Tabeknacle at:'12 o'clock. JUNE 11-AFTERNOON SESSION The meeting. Gas called -to order at 2 o'clock, with President E. H. Weitzel in- the .chair. The minutes of, the organization meeting and that of the Executive Board, the 1atier:of which was held April 15, 1913, in Denver, were read and both' approved. A letter from A. 3. Reef, of Denver, containing proposed amendments to the Constitution and By.-Laws, was read, and, upon motion,, was referred to the Executive Board, with .instructions to report upon the matter at the next, regular meeting. The proposed amendments follow: Article I1 (regarding who may become members and how) to be amended to read as follows: "Membership in this Institute shall be of three classes-corporate, individual, and honorary. Any company, firm, or individual operator actually engaged in the mining of coal within the territory of this Institute may become a corporate member on application, and by consent of a majority of the members present at any stated meeting. Any person, who is directly engaged or interested: in some branch of coal-mining may become an individual member upon application, and by consent of a majority of the members present at any stated meeting. Honorary members may be elected at the discretion of the Institute."